2018
DOI: 10.4103/wjnm.wjnm_11_17
|View full text |Cite
|
Sign up to set email alerts
|

A case of well-differentiated hepatocellular carcinoma identified on gallium-68 prostate-specific membrane antigen positron emission tomography/computed tomography

Abstract: Prostate-specific membrane antigen (PSMA) is a glycosylated type-II transmembrane protein highly expressed in certain tumor cells. To the best of our knowledge, this is the first case reported of an isolated well-differentiated hepatocellular carcinoma (HCC) strongly suspected on gallium-68 ( 68 Ga)-PSMA positron emission tomography/computed tomography (PET/CT), which was not well characterized both on magnetic resonance imaging (MRI) liver with Primovist as well as fluorine-18 ( 18 F)-choline PET/CT. Our pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…[8] In the case described by Huang et al, both AFP and PSA were within normal range and biopsy showed an encapsulated hepatocellular lesion in a cirrhotic liver. [9] In our case, the patient had raised PSA and normal AFP level in the blood. No PSMA-expressing lesion attributable to prostatic cancer was demonstrated in our case.…”
Section: Discussionmentioning
confidence: 47%
“…[8] In the case described by Huang et al, both AFP and PSA were within normal range and biopsy showed an encapsulated hepatocellular lesion in a cirrhotic liver. [9] In our case, the patient had raised PSA and normal AFP level in the blood. No PSMA-expressing lesion attributable to prostatic cancer was demonstrated in our case.…”
Section: Discussionmentioning
confidence: 47%
“…68 Ga PSMA ligand uptake in thyroid gland, lung metastasis, gastric and colonic malignancies, RCC, neuroendocrine tumor, glioma, breast cancer, gynecological malignancies, and HCC was reported in literature. 5 9 10 11 12 13 14 15 16 17 Parathyroid adenoma was included in the differential diagnosis of focal tracer uptake in a report by Pfob et al 18 In the current study, the most common 68 Ga PSMA ligand avid malignancy was lung adenocarcinoma. In addition, malignancies such as gastric adenocarcinoma, multiple myeloma, lung neuroendocrine tumor, urothelial carcinoma, HCC, colon adenocarcinoma, NSCLC showed 68 Ga PSMA ligand avidity.…”
Section: Discussionmentioning
confidence: 64%
“…5 Only a few recent case series have described PSMA uptake in primary HCC using various PSMA ligands. [6][7][8] In contrast, immunohistochemical staining in 103 cases indicated promising results for in vivo utilization of 68 Ga-PSMA PET/CT in HCC. 9 Another immunohistochemistry analysis showed high PSMA staining of the endothelial cell lining of vessels penetrated by HCC tumor cells.…”
mentioning
confidence: 99%
“…However, a higher tumor-to-liver FDG ratio has been described in presence of extrahepatic metastasis 5 . Only a few recent case series have described PSMA uptake in primary HCC using various PSMA ligands 6–8 . In contrast, immunohistochemical staining in 103 cases indicated promising results for in vivo utilization of 68 Ga-PSMA PET/CT in HCC 9 .…”
mentioning
confidence: 99%